COMPARISON OF DIET AND USE OF BROMELIADS BETWEEN A BROMELICOLOUS AND A BROMELIGENOUS ANURAN AT AN INSELBERG IN THE SOUTHEASTERN OF BRAZIL - PERTEL WESLEI; TEXEIRA ROGEIRO; FERREIRA RODRIGO (Caldasia)
Anurans from an inselberg in southeastern Brazil were studied using a sample ofsixty tank of bromeliads Alcantharea sp. We found 153 tadpoles of S. arduous, 21adults of S. arduous, 30 adults of T. miliaris, and two adults of Scinax x-signatus,which were not considered in our analyses. Tadpoles of S. arduous were present in35% of the analyzed plants. Adults of S. arduous (bromeligeneous) occurred in 25%of analyzed plants, while adults of T. miliaris (bromelicolous) occurred in 30%.Apparently the presence of toe pads in S. arduous allow them to occupy the centerportion of bromeliads, while T. miliaris, which lack pads on their toes, were foundon the base of the plant axils. The number of anuran species and the abundance ofindividuals found were low. This may be a result of the high altitude of our studiedsite or a restriction imposed by the saxicolous environment, such as high temperaturesand low humidity during the day. Both species can be considered generalist feedersdue to their wide variety of ingested prey. Formicidae was their main prey but wasabsent segregation in the bromeliads. Blattodea was very common inside the bromeliadaxils and represented the most signifi cant prey by weight in both frog species. Weconclude that both anurans forage inside and outside of bromeliads. Trophic nichebreadth in S. arduous was larger than in T. miliaris. Even both species being commoninhabitants of the same environment, they demonstrated a marked spatial segregationin the bromeliads. Based on their diet, however, there may be disputes for territoryoutside of the bromeliads.